Internet based crossover robot remote control competition among Asian countries - Development of practice based innovative education methodology, phase V - Xu, C.; Ming, A.; Kanamori, C.; Aoyama, H.; Li, H.; Xu, L.; Li, X.; Benjanarasuth, T.; Nundrakwang, S.; Purahong, B.; Wong, C.-C (2012 IEEE International Conference on Mechatronics and Automation, 2012)
We introduce 2011's progress and achievements of an internet based crossover robot remote control competition between Japan and China, Thailand, and Taiwan respectively. The competition project has two subjects: the competition itself and the student-student communication and cooperation. The basic competition mode is a remotely controlled robot via the internet cooperates with a locally controlled robot to finish a specified task and, as a unique feature of the project, the student-student communication and cooperation is trained through a crossover team organization style that each team is organized by two groups from different universities and the team members required to cooperate with each other via the internet to make robots and deal with competition affairs. Our experience shows the competition benefits not only students' technical skills but also their various no-technical skills and is expected to promote the development of a practice based university education methodology in the future.